Genetic analysis of autosomal and X-linked markers across a mouse hybrid zone - Macholán, Milos; Munclinger, Pavel; Sugerková, Monika; Dufková, Petra; Bímová, Barbora; Bozíková, Eva; Zima, Jan; Piálek, Jaroslav (Evolution; international journal of organic evolution, 2007)
In this paper, we present results of the first comprehensive study of the introgression of both autosomal and sex-chromosome markers across the central European portion of the hybrid zone between two house mouse subspecies, Mus musculus musculus and M. m. domesticus. More than 1800 individuals sampled from 105 sites were analyzed with a set of allozyme loci (hopefully representing neutral or nearly neutral markers) and X-linked loci (which are assumed to be under selection). The zone center is best modeled as a single straight line independent of fine-scale local geographic or climatic conditions, being maintained by a balance between dispersal and selection against hybrids. The width (w) of the multilocus autosomal cline was estimated as 9.6 km whereas the estimate for the compound X-chromosome cline was about 4.6 km only. As the former estimate is comparable to that of the Danish portion of the zone (assumed to be much younger than the central European one), zone width does not appear to be related to its age. The strength (B) of the central barrier was estimated as about 20 km; with dispersal (sigma) of about 1 km/gen(1/2), this means effective selection (s*) is approximately 0.06-0.09 for autosomal loci and about 0.25 for X-linked loci. The number of loci under selection was estimated as N= 56-99 for autosomes and about 380 for X-linked loci. Finally, we highlight some potential pitfalls in hybrid zone analyses and in comparisons of different transects. We suggest that conclusions about parts of the mouse genome involved in reproductive isolation and speciation should be drawn with caution and that analytical approaches always providing some estimates should not be used without due care regarding the support or confidence of such estimates, especially if conclusions are based on the difference between these estimates. Finally, we recommend that analysis in two-dimensional space, dense sampling, and rigorous treatment of data, including inspection of likelihood profiles, are essential for hybrid zone studies.
Keywords: demografie; izoenzymy; populační genetika; Genetics, Population; Demography; mikrosatelitní repetice; Europe; chromozom X; pravděpodobnostní funkce; genetické markery; Selection, Genetic; Evropa; X Chromosome; selekce (genetika); Likelihood Functions; Microsatellite Repeats; Animals; zvířata; Isoenzymes; Hybridization, Genetic; myši; hybridizace genetická; Mice; Genetic Markers